АКАДЕМІЧНЕ ПІДПРИЄМНИЦТВО В УКРАЇНІ: ПОНЯТТЯ ТА СУБ’ЄКТИ - Мачуський, Володимир Володимирович (ВЕРХОВЕНСТВО ПРАВА, 2018)
The article describes the results of the study of the legal status of subjects of academic entrepreneurship in Ukraine, clarified the state of legal support for academic entrepreneurship, defined the range of subjects of academic entrepreneurship, deepened understanding of the essence of academic entrepreneurship in the context of developing practical recommendations aimed at improving the legal support of the organization and the implementation of academic entrepreneurship in Ukraine. In the article, in particular, it is noted that the domination of entrepreneurship as a socioeconomic phenomenon in modern society caused the transformation of the role and place of universities. The evolution of forms and methods of developing and transferring knowledge led to the evolution of universities from the centers of education and freedom through research universities to entrepreneurial universities. The emergence of the newest economies (knowledge economy, digital economy, sharing economics), digital education and science has created a need, on the one hand, for the introduction of entrepreneurship as a basic competence in university education, and on the other hand, in academic entrepreneurship as a means of implementing university capacity in regional and global dimensions. The article states that academic entrepreneurship is determined depending on various criteria chosen by researchers. At the same time, the unifying component of the diverse views of academics on academic entrepreneurship is the recognition of the commercialization of scientific knowledge as the basis of academic entrepreneurship. The form and methods of transferring scientific knowledge may be different, but the commercial (business) component is decisive in the sense of academic entrepreneurship. The article also defines the concept and subjects of academic entrepreneurship. Academic entrepreneurship is a scientific, scientific and technical, innovation activity of institutions of higher education (universities), which is carried out for the achievement of economic and social results and for the purpose of profit. The subjects of academic entrepreneurship are legal entities and individuals with special status - higher educational establishments (universities) and scientists